IhChannels Contribute to the Different Functional Properties of Identified Dopaminergic Subpopulations in the Midbrain - Henrike Neuhoff; Axel Neu; Birgit Liss; Jochen Roeper (2002)
Dopaminergic (DA) midbrain neurons in the substantia nigra (SN) and ventral tegmental area (VTA) are involved in various brain functions such as voluntary movement and reward and are targets in disorders such as Parkinson's disease and schizophrenia. To study the functional properties of identified DA neurons in mouse midbrain slices, we combined patch-clamp recordings with either neurobiotin cell-filling and triple labeling confocal immunohistochemistry, or single-cell RT-PCR. We discriminated four DA subpopulations based on anatomical and neurochemical differences: two calbindin D28-k (CB)-expressing DA populations in the substantia nigra (SN/CB+) or ventral tegmental area (VTA/CB+), and respectively, two calbindin D28-k negative DA populations (SN/CB-, VTA/CB-). VTA/CB+ DA neurons displayed significantly faster pacemaker frequencies with smaller afterhyperpolarizations compared with other DA neurons. In contrast, all four DA populations possessed significant differences in I(h) channel densities and I(h) channel-mediated functional properties like sag amplitudes and rebound delays in the following order: SN/CB- --> VTA/CB- --> SN/CB+ --> VTA/CB+. Single-cell RT-multiplex PCR experiments demonstrated that differential calbindin but not calretinin expression is associated with differential I(h) channel densities. Only in SN/CB- DA neurons, however, I(h) channels were actively involved in pacemaker frequency control. In conclusion, diversity within the DA system is not restricted to distinct axonal projections and differences in synaptic connectivity, but also involves differences in postsynaptic conductances between neurochemically and topographically distinct DA neurons.